AN ANALYSIS ON THE INTERFERENCE OF MALAY IN PRONOUNCING ENGLISH VOICELESS STOPS - Nurhayati, Nurhayati; Sudarsono, Sudarsono; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Indonesian students learn English as a foreign language. They may transfer their first language into their target language. The interference can occur in various aspects like pronunciation. The purpose of this research is to find out whether or not students transfer their first language (Malay) into the target language (English) when pronouncing English voiceless stops and to find how often the transfer is made by the students. The method is Contrastive Analysis (CA). It contrasts the differences of L1 and L2 to predict and to explain the problems that learners might encounter in their target language learning. The subject of this research is the English Language Education Study Program students of Academic Year 2009/2010. Their L1 is Malay. The data were collected through direct and indirect observation. Direct observation was done to observe students’ pronunciation of words tested. Indirect observation was done by replaying the record to confirm the measurement made on the first direct checking. Native speakers’ help was also needed in this indirect observation in reanalyzing the data. Based on the result, the researcher finds that interference happens, and the frequency is quite often. It shows that even though students have learned English for years, they are still making errors in pronunciation, especially in pronouncing aspirated voiceless stop phonemes. The conclusion is that the differences between Malay and English in the sound system, especially in term of aspiration could cause interference. Key words: interference, pronunciation, English voiceless stops